Słownictwo florystyczne w powieści poetyckiej "Jan Bielecki" Juliusza Słowackiego - klasyfikacja semantyczna = Floristic vocabulary in the poetic novel "Jan Bielecki" by Juliusz Słowacki - semantic classification - Andrejczyk, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The purpose of the article is to discuss the floristic vocabulary in the poetic novel "Jan Bielecki" by Juliusz Słowacki and present the semantic classification of the indicated lexical group. This sketch discusses three circles of meaning, which oscillate around woody plants, flowering plants and other plants. In the considerations, I assume the theory of the lexical-semantic field presented by Danuta Buttler.
Keywords: Słowacki, Juliusz (1809-1849); powieść poetycka; pole semantyczne; leksyka florystyczna; poetic novel; semantic field; floristic lexis